Subsídios à gestão ambiental de parques urbanos: o caso do Parque Ecológico do Município de Belém Gunnar Vingren (PEGV) - CARDOSO, Silvia Laura Costa (Universidade Federal do Pará, 2012)
The research debates the advantages and difficulties that are intrinsic in the urban parks implementation. The central research question is: what factors may facilitate or hinder an urban park implementation in an area of significant occupational pressure? The research takes as a case study the Belem City Ecological Park Gunnar Vingren (PEGV). For analysis, the research uses the literature of participation, governance and urban governance taking as a central issue the urban parks environment management. The research also uses the stakeholders’ literature for a better understanding of social actors’ behavior. Methodologically, the research takes the qualitative method and uses direct observation and semi-structured interviews with the stakeholders. The study stresses two main conclusions. First, the research shows that different environment management patterns carried out in Belem during two different government periods had direct influence on social actors participation in the PEGV implementation and then in the way of how they interact with the park managers. Second, the implementation of two large governmental projects (Una Bay Macro-drainage Project that began in 1988 and the Centenário Avenue Extension Project that is part of the Metropolitan Action Project and started in 2010) carried out for the city urban development also contributed to make harder to conciliate the divergent interest of the urban actors.